Application of K-Means Clustering to Monitoring the level of Fertilizer Usage in Rice Fields in Ngawi Regency - Prabowo, Iwan Ady; Wijayanto, Hendro; Wantoro, Sujud Aji (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
Fertilizer is a substance given to plants that could be food for plants. FertilizerÂ itself divided into two types, thatÂ isÂ inorganicÂ fertilizersÂ andÂ organicÂ fertilizer.Â FertilizerÂ isÂ very importantÂ toÂ theÂ needsÂ of farmers,Â especiallyÂ farmers.Â ThereforeÂ fertilizerÂ needs should be ableÂ to in monitoringÂ inÂ orderÂ not to occur lack. The purpose of this study is a grouping of the use of fertilizer in every town in the districts of Ngawi with k-Means algorithm. The formulation of the problem to overcome is how to apply the method of k-meansÂ algorithmÂ toÂ categorizeÂ fertilizerÂ needsÂ inÂ everyÂ townÂ inÂ theÂ Ngawi.Â K-meansÂ isÂ clustering algorithm where one object can be in group based on data similarities. Clustering results K-means Clustering is seen in the first group high (Cluster 1) contains 6, In the second group medium (Cluster 2) contains 2 sub-districts, while in the third group low (cluster 3rd) contains 11 sub-districts.